Haemodynamics imaging of swine segmental kidney artery using duplex Doppler technique - Aleksiewicz Roman; Lutnicki Krzysztof; Bojarski Marcin; Al-Mutari Ilona; Bocheńska Aneta (Journal of Veterinary Research, 2019)
Introduction: The aim of the study was to assess the usefulness of duplex Doppler to objectify swine renal arterial flow in physiological conditions. The pig kidney was selected for its morphological similarities to the human and for the results therefore offering data to wider research. Material and Methods: Six White Large x Landrace sows, of 48.5–53 kg b.w. were used. Vascular flow parameters were acquired with a convex probe USG device with a duplex Doppler function using pulsed waves (frequency range of 5–7.5 MHz). Segmental kidney arterial flow was measured. Results: The RI values were within the 0.57 (min) to 0.6 (max) range, ̄xRI was 0.58 (±0.014), and the SD2 value was 0.0002. The PI index values ranged from 1.21 (min) to 1.3 (max), and ̄xRI was 1.24 (±0.035). The value of SD2 was 0.00123. In the S/D index, the results fell between 2.2 (min) and 2.49 (max), with ̄xS/D of 2.29 (±0.117). The value of variance SD2 was 0.0139. A double analysis of correlation between indices showed this to be almost certain and highly positive as confirmed by high correlation coefficients: r RI & PI 0.857, rhoRI & PI 0.739, rRI & S/D 0.930, rhoRI & S/D 0.941, rPI & S/D 0.913, and rhoPI & S/D 0.754. The segmental kidney arterial flow spectrum evinced falls in PSV and PSV/LDV ratio, also noticed in the filling of the spectral window, comparing the renal to an interlobar artery. Conclusion: Swine were selected because of renal anatomical and haemodynamic similarity to humans. The most relevant values and indices approximated those in humans. The study anaesthetic protocol had a minor influence on the average RI, PI, and S/D indices.